Speech and the national question in Panama between the years 1860 and 1880 - Muñoz Griffith, Vicente (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The central purpose of this article is to reveal the existence of the deep forces of a part of the Panamanian intellectual movement represented by Justo Arosemena and Pablo Arosemena that contributed to the formation of a national identity, and that not only managed to articulate an idea of nation, but which also gave rise to a profoundly Americanist discourse based on the idea of cooperative relations with other countries in the Latin American region.